Sialic acid: a sweet swing between mammalian host and Trypanosoma cruzi - Freire-de-Lima, Leonardo; Oliveira, Isadora A.; Neves, Jorge L.; Penha, Luciana L.; Alisson-Silva, Frederico; Dias, Wagner B.; Todeschini, Adriane R. (Frontiers in Immunology, 2012)
Commonly found at the outermost ends of complex carbohydrates in extracellular medium or on outer cell membranes, sialic acids play important roles in a myriad of biological processes. Mammals synthesize sialic acid through a complex pathway, but Trypanosoma cruzi, the agent of Chagas’ disease, evolved to obtain sialic acid from its host through a trans-sialidase (TcTS) reaction. Studies of the parasite cell surface architecture and biochemistry indicate that a unique system comprising sialoglycoproteins and sialyl-binding proteins assists the parasite in several functions including parasite survival, infectivity and host-cell recognition. Additionally, TcTS activity is capable of extensively remodeling host cell glycomolecules, playing a role as virulence factor. This review presents the state of the art of parasite sialobiology, highlighting how the interplay between host and parasite sialic acid helps the pathogen to evade host defense mechanisms and ensure lifetime host parasitism.